Integrasi Filosofi Tri Kaya Parisudha Dalam Penguatan Pendidikan Agama Hindu Dan Budi Pekerti Siswa Sekolah Dasar Di Kota Mataram: Integrasi Filosofi Tri Kaya Parisudha Dalam Penguatan Pendidikan Agama Hindu Dan Budi Pekerti Siswa Sekolah Dasar Di Kota Mataram - GETAS, i wayan; Arini, Ni Made (Guna Widya: Jurnal Pendidikan Hindu, 2025)
This study aims to examine the integration of the Tri Kaya Parisudha philosophy in strengthening Hindu religious education and character development among elementary school students in Mataram City. Tri Kaya Parisudha, encompassing good thoughts (manacika), good speech (wacika), and good actions (kayika), is believed to be an effective foundation for character and moral education when properly integrated into learning processes. This research employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews with Hindu religious teachers, principals, and students, as well as documentation studies at several elementary schools in Mataram. The findings reveal that incorporating the values of Tri Kaya Parisudha into teaching not only enhances students' understanding of Hindu teachings but also fosters respectful, honest, and responsible behavior in their daily lives. The study concludes that the structured and contextual application of the Tri Kaya Parisudha philosophy can serve as an effective strategy for reinforcing Hindu religious education and shaping students' character from an early age within elementary school settings.